Harmonizing Gorontalo Regional Regulations in Light of Constitutional Court Decision No. 168/PUU-XXI/2023: A Regional Approach to Foreign Worker Governance - Saldi Arief; Novendri M. Nggilu; Supriyadi A. Arief (Gemini Littera Publishing, 2026)
The governance of foreign workers has become an increasingly significant constitutional issue in Indonesia following Constitutional Court Decision No. 168/PUU-XXI/2023, which reaffirmed the need to balance investment interests with the State's constitutional obligation to protect Indonesian workers. The Decision has not only reshaped national labour policy but has also necessitated regulatory adjustments at the regional level as part of the implementation of Indonesia's decentralized governance framework. This study examines the constitutional implications of the Decision for the harmonization of Gorontalo Provincial Regulations governing foreign workers and formulates a regulatory reform framework consistent with constitutional standards. Employing normative legal research, the study applies statutory, conceptual, and case approaches through an analysis of the 1945 Constitution of the Republic of Indonesia, Law No. 6 of 2023 on Job Creation, Law No. 23 of 2014 on Regional Government, Constitutional Court Decision No. 168/PUU-XXI/2023, and Gorontalo Provincial Regulations No. 1 of 2022 and No. 8 of 2016. The findings reveal that the existing regional regulatory framework in Gorontalo remains predominantly administrative in orientation and has yet to fully internalize the constitutional standards established by the Constitutional Court, particularly concerning the prioritization of Indonesian workers, mandatory counterpart workers, measurable knowledge and technology transfer, integrated labour supervision, and effective enforcement mechanisms. The study concludes that the harmonization of regional regulations should extend beyond formal legislative conformity toward the substantive implementation of constitutional principles through a regulatory framework capable of strengthening legal certainty, protecting the national workforce, enhancing regional governmental accountability, and sustaining a conducive investment climate within Indonesia's decentralized legal system.